Review of Teaching Staff Manpower Retention and Stock in Secondary Schools - Cornelius Ofobuisi Okorie; Okechukwu Egwu Ibiam; Chiedozie P. Nwosu; Ayodeji O. Adedeji; Sunday Onele (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
For some decades, scholarly debate on manpower related issues have dominated discussions on the standard of education. This paper tried to match manpower retention and attrition with the philosophy of public secondary education in Ebonyi north senatorial zone of Ebonyi state, Nigeria. We x-rayed the manpower capacity of public secondary schools with the view to finding if the current stock would achieve the philosophy of secondary education as contained in the approved National Policy on Education in Nigeria. Specifically, our emphasis was on the manpower qualification, sufficiency, sex mix and subject specialty. Using the multi-stage sampling techniques, the study revealed significant cases of unqualified teachers in the zone, cases of insufficiency of teachers in some schools; lopsided deployment of teachers and imbalanced sex mix amongst others. Study implications in these schools were evidenced on the performances of students in external examinations and the prevailing decline in the standard of education in the zone.